PENERIMAAN SUAKA DAN PROSES MASUK PRANCIS PADA PEMERINTAHAN FRANCOIS HOLLANDE DAN EMMANUEL MACRON - Darmawan, Raka; Wardani, Abellia Anggi (Paradigma: Jurnal Kajian Budaya, 2025)
France embraces diversity in terms of religion, race, and ethnicity in its society. The arrival of migrants and foreigners, especially in the post-Second World War period contributed to France’s current demographic landscape. In dealing with the influx of population, France has adopted various immigration policies, as stated on the website of the Ministry of the Interior and Overseas, but has not significantly improved the current situation. As the immigration issue has continuously become prominent in French society, this research takes on comparing the policies carried by the governments of François Hollande and Emmanuel Macron on the issue while also taking into account their different political axes. Thus, the purpose of this study is to analyze the political discourses embedded in the immigration policies between the Hollande and Macron administrations. This research makes use of available sources from the immigration policies of both governments during their five years in office. The data was collected by employing qualitative research methods by Iosifides combined with critical discourse analysis theory by Norman Fairclough and the concept of political ideology by D. Parenteau and I. Parenteau. The findings of this research suggest that Hollande's leftist orientation contributed to his pro-people (immigrants) immigration policy, while Macron's center orientation attempted to tighten the immigration policy towards foreigners.